10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Metabolic syndrome (MetS) is increasingly prevalent due to sedentary lifestyles and late dinners in Ghana. This study in Ga North Municipal, Accra-Ghana, used an observational cross-sectional design involving 198 adult males. Findings indicated that 77.3% had knowledge on late dinners and perceived it as a harmful health effect, while 57.5% defined MetS as a cluster of diseases from metabolic activity fluctuations. Key risk factors identified included obesity (89.4%), alcohol consumption (86.4%), physical inactivity (88.9%), high salt intake (86.4%), and late dinner (89.9%). Despite this understanding, 78.8% exhibited poor prevention efforts, with 67.2% resistant to exercise and 56.6% not participating in regular health screenings. Respondents with higher educational level were more likely to have knowledge on late dinner and metabolic syndrome than those with lower educational level. The study identified a significant high level of knowledge on contributing factors of late dinners as a harmful habit in male adults. The study recommends heightened public awareness to promote prevention behaviors like exercise, dietary modification, and frequent health screenings.